Comparison of the incidence, nature and cause of injuries sustained on dirt field and artificial turf field by amateur football players - Kordi Ramin; Hemmati Farajollah; Heidarian Hamid; Ziaee Vahid (BMC, 2011)
Abstract Background Data on the incidence, nature, severity and cause of match football injuries sustained on dirt field are scarce. The objectives of this study was to compare the incidence, nature, severity and cause of match injuries sustained on dirt field and artificial turf field by amateur male football players. Methods A prospective two-cohort design was employed. Participants were 252 male football players (mean age 27 years, range 18-43) in 14 teams who participated in a local championship carried on a dirt field and 216 male football players (mean age 28 years, range 17-40) in 12 teams who participated in a local championship carried on a artificial turf field in the same zone of the city. Injury definitions and recording procedures were compliant with the international consensus statement for epidemiological studies of injuries in football. Results The overall incidence of match injuries for men was 36.9 injuries/1000 player hours on dirt field and 19.5 on artificial turf (incidence rate ratio 1.88; 95% CI 1.19-3.05). Most common injured part on dirt field was ankle (26.7%) and on artificial turf was knee (24.3%). The most common injury type in the dirt field was skin injuries (abrasion and laceration) and in the artificial turf was sprain and ligament injury followed by haematoma/contusion/bruise. Most injuries were acute (artificial turf 89%, dirt field 91%) and resulted from player-to-player contact (artificial turf 59.2%, dirt field 51.4%). Most injuries were slight and minimal in dirt field cohort but in artificial turf cohort the most injuries were mild. Conclusions There were differences in the incidence and type of football match injuries sustained on dirt field and artificial turf.